Quantum Chemistry Based Quantitative Structure-Activity Relationship Prediction Setting for Toxicity of 4-Imidazolyl-1,4-Dihydropyridines as Calcium Channel Blockers - Vahdani, Saadat; Sarem, Mohsen; Hadizadeh, Farzin (Asian Journal of Chemistry, 2012)
The usefulness of the quantum chemical descriptors, calculated at the level of the DFT theory using 6-31 + G (d,p) basis set for quantitative structure-activity relationship study of 4-imidazolyl-1,4-dihydropyridines as calcium channel blockers was examined. A dataset set of thirty six 1,4-dihydropyridines constitute a group of small organic compounds. Several types of descriptors, including electrotopological, structural, thermodynamics and quantum chemical, were used to derive a quantitative relationship between L-type calcium channel blocking activity and structural properties. Multiple linear regressions (MLR) were employed to model the relationships between molecular descriptors and biological activity of molecules using stepwise method and genetic algorithm as variable selection tools. A multi-parametric equation containing maximum five descriptors at AM1 method with good statistical qualities (R2train = 0.860, Ftrain = 28.265, Q2LOO = 0.802, R2adj = 0.829, Q2LGO = 0.792, Q2BOOT = 0.796) was obtained by multiple linear regression using stepwise method. The accuracy of the proposed MLR model was illustrated using the following evaluation techniques: cross-validation and Y-randomization.